Survival of Salmonella on Biodegradable Mulch, Landscape Fabric, and Plastic Mulch - Alyssa A. Rosenbaum; Claire M. Murphy; Annette L. Wszelaki; Alexis M. Hamilton; Steven L. Rideout; Laura K. Strawn (Journal of Food Protection)
Ground covers are used in produce production to enhance plant growth and control diseases and pests. While various factors are considered when selecting commercial ground covers, food safety, particularly the survival of foodborne pathogens, is often overlooked. This study aimed to assess the survival of Salmonella on different ground covers, including biodegradable mulch, landscape fabric, and plastic mulch. New rolls of each ground cover were cut to fit a 100 × 15 mm petri dish and spot inoculated with a seven-strain Salmonella cocktail at approximately 6 log CFU/cm2. The inoculated coupons were stored in a climate-controlled chamber (23°C, 55% relative humidity) and sampled at 0, 0.06 (1.5 h), 0.17 (4 h), 1, 2, 3, 5, 7, 30, 60, 90, and 140 days postinoculation (dpi). If counts dropped below the detection limit (<0.12 log CFU/cm2), enrichments were performed following the Food and Drug Administration’s Bacteriological Analytical Manual Salmonella protocol. Salmonella survived 140 dpi on all tested ground covers, with reductions >5 log CFU/cm2. Survival rates at 140 dpi were highest on landscape fabric (83%, 25/30) followed by plastic mulch (50%, 15/30) and biodegradable mulch (13%, 4/30) coupons (p < 0.05). During the first 30 dpi, biodegradable mulch exhibited the smallest reduction in Salmonella (2.47 ± 0.26 log CFU/cm2), compared to landscape fabric (3.07 ± 0.30 log CFU/cm2) and plastic mulch (3.86 ± 0.72 log CFU/cm2). After 60 dpi, Salmonella reductions stabilized across all materials (∼4 log CFU/cm2) and by 90 dpi, no significant differences were observed between ground cover types (p > 0.05). Although Salmonella survival varied among ground covers in the short-term (0–30 dpi), a >5 log CFU/cm2 reduction of Salmonella was observed among all materials by 140 dpi. Findings suggest that ground cover material influences Salmonella survival and should be factored into food safety risk management strategies, especially when ground covers are reused.